2022
DOI: 10.3389/fcvm.2022.981010
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms of endothelial dysfunction in Kawasaki-disease-associated vasculitis

Abstract: Kawasaki disease (KD) is an acute, inflammation mediated vasculitis, mainly affecting in children under five, which is consider as the most common coronary artery disease in children. The injuries of coronary arteries would result in dilation or thrombus formation, bringing great threaten to patients. Endothelium, located in the inner surface of coronary artery, serves as the interface between the circulating inflammatory cells and vascular media or adventitia, which is the first target of inflammatory attacks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…Many studies have shown that KD is an acute systemic vasculitis; however, the pathogenesis is still unclear, and immune disorders [4,39,40] and endothelial dysfunction [9,41] are important mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have shown that KD is an acute systemic vasculitis; however, the pathogenesis is still unclear, and immune disorders [4,39,40] and endothelial dysfunction [9,41] are important mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Vascular endothelial dysfunction involves activation of apoptotic pathways, proliferation and migration, and is central to KD-associated vasculitis. The molecular mechanisms of vascular EC injury and dysfunction in KDassociated vasculitis have been well reviewed elsewhere [84,85]. These include the role of non-coding RNAs (micro-RNAs, long non-coding RNAs), inflammatory cell activation, cytokine production, reactive oxygen species accumulation and lipid oxidation.…”
Section: Vascular Endothelial Dysfunction In Kawasaki-disease-associa...mentioning
confidence: 99%
“…Immune and non-immune cells, including macrophage/monocytes, neutrophils, and endothelial cells, express PRRs and are activated in response to PAMPs and DAMPs ( 46 , 47 ). Endothelial cells are critical for the maintenance of vascular homeostatsis ( 46 ) and play a critical role in KD vasculitis and formation of coronary artery aneurysms ( 2 , 48 , 49 ). Upon activation, they recruit circulating inflammatory cells and increase vascular cell wall permeability ( 50 ).…”
Section: Mechanisms Inducing Inflammationmentioning
confidence: 99%